Pelatihan Bahasa Visual dalam Media Sosial sebagai Branding Diri Anak-anak Panti Asuhan Dharma Laksana - I Nyoman Miyarta Yasa; Ashar Banyu Lazuardi; Mohamad Yudisa Putrajip; I Gde Anjas kharisma Nata; I Wayan Kusuma Di Biagi; Qatrunnada Qatrunnada (LPPI UMN AL WASHLIYAH, 2025)
This study investigates the effectiveness of visual language training in strengthening self-branding skills among children at the Dharma Laksana Orphanage through social media. The problem addressed in this research is the limited visual literacy and inconsistent digital identity often found in orphanage-based youth, which can hinder their ability to participate in today’s visually driven communication landscape. The training aimed to enhance their visual comprehension, content-production abilities, and confidence in developing a safe and consistent online identity. Using a participatory method, the program combined observation, content analysis, and pre–post assessments to evaluate changes in technical and psychosocial competencies. The results show substantial improvement in participants’ ability to interpret and create visual materials, articulate a personal aesthetic, and engage more confidently with digital platforms. Audience feedback also played a supportive role in reinforcing their emerging digital identities. Overall, the findings indicate that visual language training can serve as an effective empowerment strategy, helping orphanage youth build stronger self-presentation skills and participate more meaningfully in online spaces.